Stedelijk Museum Amsterdam : Moderne Kunst : Herindeling en uitbreiding van het Stedelijk. - Bertheux, Wil; Daalder, Tony; Dippel, Rini; Le Fever, Els; Joosten, Joop; Krielaart, Ton; van 't Land, Desirée; Martinet, Jan; van de Pol, Joost; de Wilde, Edy; van Droffelaar, Josine; van Oort, André; et al. (Amsterdam : Stedelijk Museum, 1978)
Appel, Karel ; Chagall, Marc ; Dibbets, Jan ; Dubuffet, Jean ; van Elk, Ger ; Fontana, Lucio ; Jorn, Asger ; de Kooning, Willem ; Lucassen ; Malevich, Kasimir ; Matisse, Henri ; Mondriaan, Piet ; Newman, Barnett ; Rietveld, Gerrit ; Ryman, Robert ; de Saint-Phalle, Niki ; Schoonhoven, Jan ; Werkman, H.N.
Nederlands & Engels
boek